2015
DOI: 10.1128/aac.05009-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pre-Antibiotic Era Klebsiella pneumoniae Isolates with Respect to Antibiotic/Disinfectant Susceptibility and Virulence in Galleria mellonella

Abstract: The EGD Murray collection consists of approximately 500 clinical bacterial isolates, mainly Enterobacteriaceae, isolated from around the world between 1917 and 1949. A number of these "Murray" isolates have subsequently been identified as Klebsiella pneumoniae. Antimicrobial susceptibility testing of these isolates showed that over 30% were resistant to penicillins due to the presence of diverse bla SHV ␤-lactamase genes. Analysis of susceptibility to skin antiseptics and triclosan showed that while the Murray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…The available data suggest that no particular virulence factor of CG23 is necessary or sufficient for invasive disease. Three liver abscess strains lacked ICEKp, and it was recently reported that the 1932 Murray Collection isolate lacking ICEKp is highly virulent in the Galleria mellonella infection model 37 . Both asymptomatic carriage isolates in our study lacked ICEKp, however the significance of this is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available data suggest that no particular virulence factor of CG23 is necessary or sufficient for invasive disease. Three liver abscess strains lacked ICEKp, and it was recently reported that the 1932 Murray Collection isolate lacking ICEKp is highly virulent in the Galleria mellonella infection model 37 . Both asymptomatic carriage isolates in our study lacked ICEKp, however the significance of this is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 83 CG23 genome sequences from our curated collection (six finished and 77 draft genomes, see Table S1 26,38 ). These included 43 genomes from our own previous studies 19,21,27,69 and 40 publicly available genomes including the 27 analysed by Struve et al 28,29,37,68,[70][71][72][73][74] . We also sequenced 15 novel genomes that were identified as ST23 by MLST (02A029, 12A041 and 16A151 14 ) or identified as K1 by classical serotyping and then confirmed as ST23 by genome sequencing (12 strains isolated between 1980 and 1987 from samples from horses; see Table S1).…”
Section: Genome Collectionmentioning
confidence: 99%
“…The K. pneumoniae isolates used in this study are clinical strains with a variety of antibiotic resistance markers, e.g., bla NDM-1 and bla SHV-18 , and have been described previously (9,10,44). K. pneumoniae was adapted to chlorhexidine as described in a previous study (9).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The recent outbreaks of carbapenemase-producing K. Pneumonia are of great importance. [3][4][5] Chlorhexidine was first introduced commercially in the United Kingdom as a disinfectant and topical antiseptic in 1954.…”
mentioning
confidence: 99%